Improving Critical Thinking Skills and Collaboration Skills Using Problem Based Learning Models, DNGM Models, Wordwall Media and Dragon Games - Fahri Fajrul Falah; Zain Ahmad Fauzi; Annisa Hasanah; Norma Paulina; Asyfa Nabila; Linda Rosydah (International Journal of Multilingual Education and Applied Linguistics, 2024)
The problem of this research is that there is still a lack of student activity in participatory learning as well as interaction and collaboration between students in group learning activities. In this research, Classroom Action Research (PTK) was carried out in three meetings. The subjects of this research were 25 class V students of SDN Antasan Besar 7 Banjarmasin. The measure of research success with learning completeness is that 80% of students achieved a KKM score above 80. The results of this research show that at Meeting I to Meeting III there was an increase in the acquisition of learning activities in the application of the learning model, resulting in the "Very Active" criteria at Meeting I, II and III. At Meetings II and III, learning activities increased to almost all very active. Students' critical thinking skills increased to almost all highly skilled at Meetings II and III. At Meetings II and III, students' collaboration skills increased to Almost All Skilled. Meanwhile, completeness of learning outcomes increased again to 100% at Meeting III. From the results of this research, it can be concluded that educators' activities experienced a very significant increase when implementing the PBL model supported by DNGM using Wordwall media and the Dragon Snake game, as well as student activities, critical thinking skills, collaboration skills, and learning outcomes.